2016
DOI: 10.1111/head.12746
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatment Therapies for Pediatric Migraine: A Qualitative Systematic Review

Abstract: Of the available evidence, ibuprofen, prochlorperazine, and certain triptan medications are the most effective and safe agents for acute management of migraine and other benign headache disorders in the pediatric population. Additional studies in this population are needed, and should take into consideration variables such as dosing, co-administered medications, treatment duration, and length of treatment effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…A recent systematic review evaluated the efficacy and safety of available treatments for children with migraine or benign primary headache in the ED [65]. The authors concluded that ibuprofen, prochlorperazine, and certain triptan medications were the most effective and safe medications for the acute management of migraine and other benign headache disorders in children in the ED [65].…”
Section: Migrainementioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review evaluated the efficacy and safety of available treatments for children with migraine or benign primary headache in the ED [65]. The authors concluded that ibuprofen, prochlorperazine, and certain triptan medications were the most effective and safe medications for the acute management of migraine and other benign headache disorders in children in the ED [65].…”
Section: Migrainementioning
confidence: 99%
“…A recent systematic review evaluated the efficacy and safety of available treatments for children with migraine or benign primary headache in the ED [65]. The authors concluded that ibuprofen, prochlorperazine, and certain triptan medications were the most effective and safe medications for the acute management of migraine and other benign headache disorders in children in the ED [65]. The authors considered the following triptans effective in adolescents: almotriptan, rizatriptan, zolmitriptan by nasal spray, sumatriptan by nasal spray, and a combination of sumatriptan and naproxen [65].…”
Section: Migrainementioning
confidence: 99%
See 2 more Smart Citations
“…Even in the highest impact journals, many trialists continue to inadequately report or calculate sample sizes . In the headache literature, one needs to look no further than recent systematic reviews to understand the commonality of underpowered studies …”
mentioning
confidence: 99%